2001
DOI: 10.1093/carcin/22.7.1027
|View full text |Cite
|
Sign up to set email alerts
|

Parous rats regain high susceptibility to chemically induced mammary cancer after treatment with various mammotropic hormones

Abstract: Parity in humans and rats provides significant protection against mammary tumor development. This study was carried out to investigate whether treatment of parous rats with mammotropic hormones would affect methyl-nitrosourea (MNU)-induced mammary carcinogenesis. Parous rats were treated with 17beta-estradiol (E2), progesterone (P4) and thyroxine (T4) alone or in combination. E2 (20 microg/60 days) and P4 (20 mg/60 days) were administered by silastic tubing and T4 in the drinking water (3 microg T4/ml). Hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
6
20
0
Order By: Relevance
“…These experiments, performed in the pre-and post-treatment models, definitely demonstrate that pregnancy primarily delays progression. Along these lines, the provocative experiments by Thordarson et al (2001), that continuing the same doses of hormones for an extended period of time (20 rather than 3 weeks) results in abundant tumor development equivalent to the AMV, indicate that hormones can promote progression, if administered continuously. A similar conclusion was reached in the parous mouse using pituitary isografts as the source of hormones .…”
Section: Mechanisms Of Protection Initiation Vs Promotionmentioning
confidence: 98%
“…These experiments, performed in the pre-and post-treatment models, definitely demonstrate that pregnancy primarily delays progression. Along these lines, the provocative experiments by Thordarson et al (2001), that continuing the same doses of hormones for an extended period of time (20 rather than 3 weeks) results in abundant tumor development equivalent to the AMV, indicate that hormones can promote progression, if administered continuously. A similar conclusion was reached in the parous mouse using pituitary isografts as the source of hormones .…”
Section: Mechanisms Of Protection Initiation Vs Promotionmentioning
confidence: 98%
“…Furthermore, the splenocytes of parous rats have significantly higher cytotoxic activity against mammary tumor cells when compared with virgin controls (29). It has been reported that parous rats have decreased levels of mammogenic hormones, and this decrease has been attributed to the decreased incidence of mammary cancers in these animals (30,31). In our laboratory, we had shown that differentiation of the mammary gland alone was not enough to confer protection against mammary cancer (23).…”
mentioning
confidence: 95%
“…There are now data indicating that progesterone could also play a pivotal role in tumorigenesis. It was shown that progestins have a role in the initiation and/or progression of rat and mouse mammary tumors (Lydon et al, 1999;Thordarson et al, 2001;Lanari and Molinolo, 2002). However, clinical and epidemiological investigations remain controversial concerning the exact implication of progesterone in breast tumorigenesis in women, and the risk of use progestin in addition to estrogen in postmenopausal hormone replacement therapy is still being debated.…”
Section: Introductionmentioning
confidence: 99%